Ubiquitin-proteasome system in Plasmodium: a potential antimalarial target to overcome resistance – a systematic review - Gonçalves, Adriana F.; Lima-Pinheiro, Ana; Ferreira, Pedro E. (Frontiers in Medicine, 2024)
Background: Malaria is a devasting parasitic disease that causes over half a million deaths every year. The necessity for prompt and thorough antimalarial drug discovery and development is accelerated by the rise in multidrug resistance and the lack of an effective vaccine. The Plasmodium spp. proteasome represents a prospective target for antimalarial treatment since several chemotherapy types have been shown to potently and selectively limit the growth of parasites. Combined with first-line artemisinin medicines, it creates synergy, even in the artemisinin-resistant parasites.Methods: PRISMA guidelines were used in the development of this systematic review. A literature search was performed in March 2024 in PubMed, Science Direct, and Scopus databases, with the following keywords: ((antimalarial resistance) AND (plasmodium OR malaria) AND (proteasome)) NOT (cancer [Title/Abstract]). Only articles with the susceptibility assessment were included.Results: Herein, 35 articles were included in the systematic review, which was divided into two subcategories: those that studied the UPS inhibitors, which accounted for 25 articles, and those that studied genetic modifications, including knockouts, knockdowns, and mutations, in the UPS towards antimalarial resistance, accounting for 16 articles. 6 articles included both subcategories. In total, 16 categories of inhibitors were analyzed, together with two knockdowns, one knockout, and 35 mutations.In this study, we reviewed the literature for available inhibitors and their respective susceptibility and ability to develop resistance toward Plasmodium spp. 26s proteasome. The proteasome was highlighted as a potential antimalarial target and as an artemisinin partner drug. However, host toxicity and susceptibility to resistance appear as the main obstacle in the development of highly potent drugs, indicating a need for additional scrutiny during any further drug development efforts.